7(y+6)-4(3-y)=19

Simple and best practice solution for 7(y+6)-4(3-y)=19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(y+6)-4(3-y)=19 equation:



7(y+6)-4(3-y)=19
We move all terms to the left:
7(y+6)-4(3-y)-(19)=0
We add all the numbers together, and all the variables
7(y+6)-4(-1y+3)-19=0
We multiply parentheses
7y+4y+42-12-19=0
We add all the numbers together, and all the variables
11y+11=0
We move all terms containing y to the left, all other terms to the right
11y=-11
y=-11/11
y=-1

See similar equations:

| 4x-8-(x-2)=x-7 | | X+2x+10+2x-30=180 | | 2,8-3,2x=-4,8-5,1x | | (3y-20)/5=0 | | 57+v=4v | | 3y-20/5=0 | | X+2x+10+2x-20=180 | | 6x2=121 | | 3(8+y)=3y+15 | | 2(7-2w)=60 | | x*3-92=92 | | 2(2w-7)=60 | | 5x+4=8+3x | | -11x/11=-98/11 | | z^2+14z+35=-35 | | 3(x-2)-5(2x-3)=22 | | x/100×40=48 | | -8=8(2m+7) | | 2x-1,5(x-1)=3 | | 3m-12=m-5 | | 8x-26+5x-27=90 | | -9m-12=24 | | 3y+8=-4y+9 | | x=(8)-9 | | 2x+3=13-3 | | x=(-8)-9 | | x=(-9+5) | | T(n)=2n^2+3 | | 2(l-12)+2l=156 | | T(n)=1/2n | | 3-2(1-x)=-2(2x=1) | | 7/(x+1)=9/(x-3) |

Equations solver categories